BIOLOGY OF THE LARGE SNAKE-HEAD OPHICEPHALUS MARULWS; (HAM.) IN BHAVANISAGAR WATERS - Devaraj, M (Indian Journal of Fisheries, 2011)
Lengthfrequency distribution of OpA/cepAa/(«war«/i«i(Hani.)fromPoongar Swampdissected out by probability plot technique produced fouryear classes, von Bertalanffy'sgrowth equation adequately describes the growth of O. marulius. The mean length atfirst maturity is 460 mm in females and 550 miu in males. The Im/Loo value for the formeris 0.41 and for the latter 0.45. A rapid fall in fecundity is observed in olderfishes (4 yearand above). Peak spawning occurs during November and December in the swamp butduring June and July in theriver and reservoir. Parental care ceases when the young onesare 4-month old. Fish less than 50mm long feed on zooplankton especially Dapfiniabnithose 50 to 110mm long prey upon Macrohrachium and larger insect nymphs